The philosophy of physical education a new perspective - Stolz, Steven A. (London Routledge, Taylor & Francis Group, 2014)
The discipline area of physical education has historically struggled for legitimacy, sometimes being seen as a non-serious pursuit in educational terms compared to other subjects within the school curriculum. This book represents the first attempt in nearly thirty years to offer a coherent philosophical defence and conceptualisation of physical education and sport as subjects of educational value, and to provide a philosophically sound justification for their inclusion in the curriculum. The book argues that rather than relegating the body to "un-thinking" learning, a person's essential being is not confined to their rationality but involves an embodied dimension. It traces the changing conceptions of the body, in philosophy and theology, that have influenced our understanding of physical education and sport, and investigates the important role that embodiment and movement play in learning about, through and in physical education. Physical education is defended as a vital and necessary part of education because the whole person goes to school, not just the mind, but the thinking, feeling and acting facets of a person. It is argued that physical education has the potential to provide a multitude of experiences and opportunities for students to become aware of their embodiment, explore alternative modes of awareness and to develop insights into and new modes of being not available elsewhere in the curriculum, and to influence moral character through the support of a moral community that is committed to that practice. Representing a sophisticated and spirited defence of the educational significance and philosophical value of physical education and sport, this book will be fascinating reading for any advanced student or researcher with an interest in physical education, the philosophy of sport or the philosophy of education.
Chapter 1. On Justifications of Sport and Physical Education: Are There Good Reasons for the Inclusion of Sport and Physical Education Within Educational Institutions? Chapter 2. Philosophical and Theological Positions of the Body: Changing Concepts of the Body and Its Influence Upon Sport and Physical Education Chapter 3. The Unique Place of Physical Education Within Education: The Fluid Concept of Education and the Process of Being "Physically Educated" Chapter 4. The Phenomenon of Play and Its Educational Significance in Physical Education: Why Do Philosophers Talk So Much About Play, Games and Sports? Chapter 5. The Moral Aspects of Sport and Physical Education: Do Sport and Physical Education Provide Unique Opportunities to Develop Moral Character? Chapter 6. MacIntyre, Rival Traditions and Physical Education
Includes bibliographical references and index.
Keywords: Physical education and training -- Philosophy